DETEKSI POLA TANGAN PADA AREA REGION OF INTEREST (ROI) DENGAN FITUR CONVEXITY DEFECTS - Sugiyatno; Untung Subagyo (LPPM STMIK El Rahma Yogyakarta, 2019)
The need for human interaction with computers today does not only use a keyboard or mouse, but has used other devices such as touch screens. However, the interaction still uses touch between the device and the user. Interaction without using touch or direct interaction is still not widely used. Like the use of a camera as an interaction tool, it is still very rarely used. The solution offered is to make a system modeling that is able to detect patterns of hand movements with the camera. The detection results can then be used as controls or as a trigger instrument for a process.